Combustion of lean methane over Co3O4 catalysts prepared with different cobalt precursors. Issue 8 (28th January 2020) - Zheng, Yifan; Yu, Yueqin; Zhou, Huan; Huang, Wanzhen; Pu, Zhiying
Abstract : The effects of cobalt precursor on the microstructure, surface properties, reducibility and catalytic performance for methane combustion were investigated. Abstract : To investigate the effect of catalyst precursors on physicochemical properties and activity of lean methane catalytic combustion, a series of Co3 O4 catalysts were prepared via a precipitation method by using four different cobalt precursors: Co(C2 H3 O2 )2, Co(NO3 )2, CoCl2, and CoSO4 . The catalysts were characterized by BET, XRD, SEM, Raman, XPS, XRF, O2 -TPD and H2 -TPR techniques. It was found that the different types of cobalt precursor had remarkable effects on the surface area, particle size, reducibility and catalytic performance. In contrast, the Co3 O4 -Ac catalyst showed a relatively small surface area, but its activity and stability were the highest. XPS, Raman, O2 -TPD and H2 -TPR results demonstrated that the superior catalytic performance of Co3 O4 -Ac was associated with its higher Co 2+ concentration, more surface active oxygen species and better reducibility. In addition, the activity of the Co3 O4 -S catalyst reduced significantly due to the residual impurity SO4 2−, which could reduce the concentration of surface adsorbed active oxygen species and inhibit oxygen migration.